2018
DOI: 10.1111/jicd.12337
|View full text |Cite
|
Sign up to set email alerts
|

Apically extruded debris during the removal of canal filling material from root canals using three techniques

Abstract: The canal filling technique used affected the amount of AED produced during the removal of canal filling material, but not sealer type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 31 publications
1
28
2
1
Order By: Relevance
“…Single-rooted teeth were used in more than 80% of the studies. 7,[9][10][11][12][23][24][25][26][27][28][29][30][31][32][36][37][38]40,41,[94][95][96][97][98][99][100][101][102][103][104][105]108,[110][111][112][113][114] Only seven studies preferred to use molar teeth 4,8,34,35,39,106,107 and one study did not provide information regarding the tooth type used. In more than 60% of the studies, researchers preferred to use straight roots/root canals (curvature < 10°) 4,7,[9][10][11]…”
Section: Resultsmentioning
confidence: 99%
“…Single-rooted teeth were used in more than 80% of the studies. 7,[9][10][11][12][23][24][25][26][27][28][29][30][31][32][36][37][38]40,41,[94][95][96][97][98][99][100][101][102][103][104][105]108,[110][111][112][113][114] Only seven studies preferred to use molar teeth 4,8,34,35,39,106,107 and one study did not provide information regarding the tooth type used. In more than 60% of the studies, researchers preferred to use straight roots/root canals (curvature < 10°) 4,7,[9][10][11]…”
Section: Resultsmentioning
confidence: 99%
“…However, earlier studies[ 1 , 19 , 22 , 23 ] have demonstrated that evaporation does not affect the final extruded debris’ weight. The canals were irrigated with water that had minimal elements that may interrupt with the weighing of the extruded materials.…”
Section: Discussionmentioning
confidence: 97%
“…[ 16 ] Many studies have utilized the exact method of the authors. [ 17 - 22 ] However, the current study has adjusted few parameters that are modified to enable proper collection of the extruded material for the included file systems. The conditions that simulated the normal clinical instrumentation were practiced in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Because high temperature can influence the setting time, flow and porosity of iRoot SP, it is usually indicated for the single-cone technique [ 15 ]. Canals obstructed with the single-cone technique always contain a larger amount of sealer than those treated with other filling techniques, such as lateral and warm vertical techniques [ 16 ]. Some researchers have demonstrated that BC sealer resulted in more residual filling materials than AH Plus in root canal retreatment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%